Two promising Bacillus-derived antifungal lipopeptide leads AF4 and AF5 and their combined effect with fluconazole on the in vitro Candida glabrata biofilms - Madhuri, Madduri; Rudramurthy, Shivaprakash M.; Roy, Utpal (Frontiers in Pharmacology, 2024)
Introduction:Candida species are endowed with the ability to produce biofilms, which is one of the causes of pathogenicity, as biofilms protect yeasts from antifungal drugs. Candida glabrata (Nakaseomyces glabrata) is one of the most prevalent pathogenic yeasts in humans and a biofilm producer. Methods: The study was aimed at evaluating the combined effects of two highly promising antifungal biomolecules (AF4 and AF5) lipopeptide in nature, chromatographically purified to homogeneity from Bacillus subtilis (B. subtilis) and the standard antifungal fluconazole (at different concentrations) to demonstrate C. glabrata biofilm formation inhibition. Biofilm production and inhibition were evaluated by quantification of the biofilm biomass and metabolic activity using crystal violet (CV) staining and XTT reduction assays, respectively. Microscopic techniques such as confocal scanning laser microscopy (CSLM) and scanning electron microscopy (SEM) were employed to visualize biofilm formation and inhibition. Results and Discussion: Compared to untreated and fluconazole-treated biofilms, an enhanced in vitro anti-biofilm effect of the antifungal lipopeptides AF4/AF5 alone and their combinations with fluconazole was established. The lipopeptides AF4/AF5 alone at 8 and 16 μg/mL exhibited significant biomass and metabolic activity reductions. SEM and CSLM images provided evidence that the lipopeptide exposure results in architectural alterations and a significant reduction of C. glabrata biofilms, whereas (2′, 7′-dichlorofluorescin diacetate (DCFDA) and propidium iodide (PI) analyses showed reactive oxygen species (ROS) generation along with membrane permeabilization. The estimation of exopolysaccharides (EPS) in AF4/AF5-treated biofilms indicated EPS reduction. The combinations of fluconazole (64/128 μg/mL) and AF4/AF5 lipopeptide (16 μg/mL) were found to significantly disrupt the mature (24 h) biofilms as revealed by CSLM and SEM studies. The CSLM images of biofilms were validated using COMSTAT. The FTIR-analyses indicate the antibiofilm effects of both lipopeptides on 24 h biofilms to support CSLM and SEM observations. The combinations of fluconazole (64/128 μg/mL) and AF4/AF5 lipopeptide were found to disrupt the mature biofilms; the study also showed that the lipopeptides alone have the potentials to combat C. glabrata biofilms. Taken together, it may be suggested that these lipopeptide leads can be optimized to potentially apply on various surfaces to either reduce or nearly eradicate yeast biofilms.